Utilización del aloe vera (Aloe Barbadensis Miller) en la elaboración de queso de chancho para mejorar la calidad nutricional - Cabrera Paredes, Luis Fernando (2016)
The topic which has been investigated was to analyze the nutritional value of the extracted aloe vera extracted from the sabila Aloe Barbadensis Miller in cheese of pork. The gel has numerous nutritional values such as vitamins, minerals, essential amino-acids that promote useful properties for human beings. Pork´s cheese was made with quality standards for processing the food product following the B.P.M. that ensure the safety of the final product. After the preliminary tests the addition of aloe vera in the different treatments in percentages of 10, 20 and 30% of gel with a blank control for comparison parameters are determined. The microbiological analysis of the product was also conducted to diagnose stability which were executed at 8, 15 and 30 days showed results that were within the limit permitted by NORMA NTE INEN 1338 for cooked meat products. The research results lined that the addition of aloe vera reported protein increases the nutritional value of the final product, increasing 15.35 0% 17.01 aloe vera 30%. Also was observed that adding this gel the fat content decreases from 20.38 to 0% aloe vera 13.34 30% by the high amount of moisture in the gel is 90%, which in this case is beneficial for the high-fat cheese. Finally was demonstrated that by sensory analysis aloe vera does not affect significantly the palatability of the product.